Regional variation and determinants of vitamin D status in sunshine-abundant Thailand - La-or Chailurkit (2017)
Background: Vitamin D insufficiency is highly prevalent. Most of the studies concerning vitamin D status were generated from countries situated at temperate latitudes. It is less clear what the extent of vitamin D insufficiency is in countries situated in the tropics and how geographical regions within country would affect vitamin D status. In the present study, we investigated vitamin D status in Thais according to geographical regions and other risk factors. Methods: Subjects consisted of 2,641 adults, aged 15 - 98 years, randomly selected from the Thai 4th National Health Examination Survey (2008-9) cohort. Serum 25 hydroxyvitamin D were measured by liquid chromatography/ tandem mass spectrometry. Data were expressed as mean ± SE. Results: Subjects residing in Bangkok, the capital city of Thailand, had lower 25(OH)D levels than other parts of the country (Bangkok, central, northern, northeastern and southern regions: 64.8 ± 0.7, 79.5 ± 1.1, 81.7 ± 1.2, 82.2 ± 0.8 and 78.3 ± 1.3 nmol/L, respectively; p < 0.001). Within each region, except for the northeastern part of the country, subjects living inside municipal areas had lower circulating 25(OH)D (central, 77.0 ± 20.9 nmol/L vs 85.0 ± 22.1 nmol/L, p < 0.001; north 79.3 ± 22.1 nmol/L vs 86.8 ± 21.8 nmol/L, p < 0.001; northeast 84.1 ± 23.3 nmol/L vs 87.3 ± 20.9 nmol/L, p = 0.001; south, 76.6 ± 20.5 nmol/L vs 85.2 ± 24.7 nmol/L, p < 0.001). Overall, the prevalence of vitamin D insufficiency was 64.6%, 46.7%, and 33.5% in Bangkok, municipal areas except Bangkok, and outside municipal area in other parts of the country, respectively. In addition, the prevalence of vitamin D insufficiency according to geographical regions was 43.1%, 39.1%, 34.2% and 43.8% in the central, north, northeast and south, respectively. After controlling for covariates in multiple linear regression analysis, the results showed that low serum 25(OH)D levels were associated with being female, younger age, living in urban and Bangkok. Conclusions: Vitamin D insufficiency is common and varies across geographical regions in Thailand.